2013
DOI: 10.2967/jnumed.113.119966
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of 18F-LMI1195 for In Vivo Imaging of Pheochromocytoma in the MENX Tumor Model

Abstract: We evaluated 18 F-LMI1195 (1-(3-bromo-4-(3-18 F-fluoro-propoxy)benzyl) guanidine), a metaiodobenzylguanidine (MIBG) analog, for the detection of pheochromocytoma in a preclinical in vivo model of endogenous neuroendocrine tumors (multiple endocrine neoplasia [MENX]). Methods: Adrenal uptake kinetics of 18 F-LMI1195 were evaluated in healthy Wistar rats (n 5 6) by dynamic PET imaging. Distribution of 18 F-LMI1195 was evaluated in tumor-bearing MENX mut/mut rats (n 5 10) and control MENX wild-type rats (n 5 4) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…Furthermore, clinical phase 1 trial of [ 18 F]LMI1195 has demonstrated the tolerance and safety in humans but with a higher effective dose than [ 123 I]MIBG [17]. Similar to the application of [ 123 I]MIBG in endocrine tumours, it shows high and specific accumulation in pheochromocytomas, which represented another potential clinical application [37]. Of note, in a recently published comparison of [ 18 F]LMI1195 with [ 11 C]HED, preliminary data suggests a comparable estimates of cardiac sympathetic innervation but offers more favourable kinetics for early cardiac imaging [38], which shows the way to further clinical phase 2 trial in predicting arrhythmic events (NCT03493516).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clinical phase 1 trial of [ 18 F]LMI1195 has demonstrated the tolerance and safety in humans but with a higher effective dose than [ 123 I]MIBG [17]. Similar to the application of [ 123 I]MIBG in endocrine tumours, it shows high and specific accumulation in pheochromocytomas, which represented another potential clinical application [37]. Of note, in a recently published comparison of [ 18 F]LMI1195 with [ 11 C]HED, preliminary data suggests a comparable estimates of cardiac sympathetic innervation but offers more favourable kinetics for early cardiac imaging [38], which shows the way to further clinical phase 2 trial in predicting arrhythmic events (NCT03493516).…”
Section: Discussionmentioning
confidence: 99%
“…18 F-LMI1195 was used in imaging of regional cardiac sympathetic denervation in the rabbit model due to its high association with NET (Yu et al 2012). Comparable to either MIBG or HED, LMI1195 has also showed high and specific accumulation in neuroendocrine tumors in the rat model, and more favorably than the reference MIBG (Gaertner et al 2013). Following a successful phase 1 clinical trial, in which 18 F-LMI1195 has demonstrated cardiac imaging potential with comparable radiation dose and favorable kinetics (Sinusas et al 2014), it was compared with 11 C-HED in a recent publication.…”
Section: F-lmi1195mentioning
confidence: 99%
“…18 F-L-6-fluoro-3,4-dihydroxyphenylalanine ( 18 F-DOPA), targeting the aromatic amino acid transporter and L-amino acid decarboxylase (Hoegerle et al 2002;Havekes et al 2008;Martiniova et al 2012), and 68 Ga-labeled somatostatin analogs (e.g., 68 Ga-DOTATOCand 68 Ga-DOTATATE), targeting somatostatin receptors (Win et al 2007), can also be used to visualize pheochromocytomas in man. We could demonstrate that the rats tumors can be noninvasively visualized using 131 I-MIBG (Gaertner et al 2013), 68 Ga-DOTATOC and 11 C-Hydroxyephedrine (HED; a norepinephrine analog) (Miederer et al 2011), 18 F-DOPA (unpublished), as well as a novel norepinephrine analog, 18 F-LMI1195 (Gaertner et al 2013). For all these tracers, higher uptake was observed in mutant rats bearing adrenomedullary tumors compared to wild-type adrenal glands.…”
mentioning
confidence: 94%